DESIGN AND IMPLEMENTATION OF AN X DOUBLE BAZOOKA ANTENNA IN A HYBRID COMMUNICATION SYSTEM - Agik Septhiani; Hesty Fitriana; Budi Basuki Subagio; Tahan Prahara; Eko Supriyanto; Eni Dwi Wardihani; Agus Rochadi; Muhlasah Novitasari Mara (Politeknik Negeri Semarang, 2025)
The double bazooka antenna is an antenna developed for military applications and later adapted by amateur radio enthusiasts for high-frequency (HF) communication. The double bazooka antenna consists of two elements: the main element, which functions as the transmitter element that transmits and receives radio frequency (RF) signals, and the auxiliary element, which serves to widen the bandwidth. The main element is the most significant factor influencing the antenna’s parameter characteristics. This study aims to realize a double bazooka antenna with a semi-directional radiation pattern at an operating frequency of 433 MHz, which will be applied as an external antenna in a hybrid communication system. The antenna material used in this study is RG-8 cable with a relative permittivity (εᵣ) of 2.3. Antenna parameter testing was conducted at the Telecommunication Engineering Laboratory of the State Polytechnic of Semarang using a Spectrum Analyzer, Vector Network Analyzer, Radio Frequency Generator, and Antenna Trainer Kit. The results of the double bazooka antenna parameter testing showed a return loss value of -23,345537 5 and a VSWR of 1:1.24 at a frequency of 433 MHz, which is in accordance with standards, and has a gain of 19.55 dBi with a semi-directional radiation pattern and vertical elliptical polarization. The double bazooka antenna was successfully implemented in a hybrid communication system, with test results showing that the antenna operates optimally. Keywords: double bazooka antenna, radio communication, hybrid communication system, handy talkie